From paper surveys to chatbots: Advancing digital monitoring of diet quality in Guatemala - Jimenez Rodas, Daniel; Ramos, Gresia; Lizarazo, Miguel; Arce, Daniela; Bonilla, Melissa (2025)
Since 2022, a network of partners has been consolidated in the Eastern and Western regions of Guatemala with the aim of strengthening diet quality monitoring among vulnerable populations, particularly in rural communities. The use of widely adopted digital tools, such as WhatsApp, has proven to be a key resource. Through a chatbot, the delivery of the Diet Quality Questionnaire (DQQ) has been efficient in terms of both time and resources.